The pathophysiology of pneumoperitoneum - Rosenthal, Raul J; Friedman, Richard L; Phillips, Edward H (Springer, 1998)
Increased intra abdominal pressure as used in laparoscopic surgery produces various changes in the human organism. This book provides surgeons and anesthesiologists with a complete overview on these changes and the consequences for the patient in the perioperative and postoperative period. Special emphasis is laid on the management of pneumoperitoneum related complications.
Keywords: patologie; pneumologie a ftizeologie; pneumoperitoneum; Pneumoperitoneum